El fuera bordismo y el turismo de aventura en el cantón Vinces - Loor Moyano, María Rosa (2022)
The realization of this case study is motivated, because in the Vinces canton a problem has been found that afflicts the entire Vinceña society, which is the scarce promotion of outboarding, an activity that is essential for adventure tourism in Vinces. Reason why this research aims to analyze the practice of outboarding as a contribution to adventure tourism in the Vinces canton. To achieve the objective of the case study, research techniques such as observation have been used, which was essential in discovering the problem, being necessary to understand and have a general idea of the project; Another technique used was the survey, which turned out to be of vital importance to know the criteria of society, in addition to being a support to check and contrast the results obtained with the previous technique; Finally, a bibliography of recent books, research and magazines was extracted in which the aspects and characteristics obtained through the categorization of the variable were supported. Among the results obtained from this research, it can be mentioned that outboarding is an activity that has arisen in Vinces since 1957 thanks to the ideas brought from abroad by Rogelio Jordán Rodríguez and that brings together locals and foreigners, this race generates economic income, although in the In recent years, the number of visitors has decreased significantly, and adventure tourism represents one of the types of tourism that has become very popular, offering many benefits, including the economic development of the town.